HUMAN RESOURCES STRATEGY: REQUIREMENTS FOR IMPLEMENTING ORGANIZATIONAL GOVERNANCE IN THE IRAQI MINISTRY OF YOUTH AND SPORTS AND DERIVING DEVELOPMENT PRIORITIES - Roula Adil Jawad; Dr. Mourad Mohammed Bahloul (Scholars Digest Publishing, 2025)
The study aimed to identify the gaps and needs in the implementation of organizational governance from a human resources perspective within the Iraqi Ministry of Youth and Sports, and to determine the most prominent factors affecting its effectiveness. The research also sought to develop a skill-based and structural framework that links human resource policies with governance strategies, including standards, procedures, and mechanisms for measurement and follow-up. The researcher adopted a descriptive methodology using the survey approach, employing questionnaires, personal interviews, and online tools to suit the nature of the study and to fulfill its objectives and research questions. A purposive sampling method was used, involving 276 individuals, selected from employees of the Ministry of Youth and Sports as well as stakeholders interacting with the Ministry, including clubs and sports federations in Iraq. A pilot study was conducted on 23 participants, while the main study included 253 participants. The data were collected and statistically analyzed using the Statistical Package for the Social Sciences (SPSS v.25). The study concluded that there are structural gaps in linking human resource policies with governance strategies, leading to lack of coordination and confusion in allocating human resources according to organizational priorities. One of the most important recommendations was to develop a comprehensive framework for organizational governance that integrates human resources with governance strategies, through the evaluation mechanisms to ensure the application of standards across the Ministry and its sub-units. establishment of unified policies, measurement procedures, and monitoring and
Keywords: Human resources strategy, its full potential, used for development.